Sistema de fichas de control médico ocupacional y periódico para el análisis de riesgo laboral acumulado de los docentes y servidores de la Universidad Técnica de Cotopaxi. - Cuyo Montes, Mayra Nataly (2018)
The present project is about the development and implementation of a computer system, which allows systematizing the medical assessment processes that are currently performed in an electronic area in the Occupational Medical Department of the Technical University of Cotopaxi. This system is directed by Dr. Richard Pérez, Occupational Physician of the institution, allowing him to optimize several of his processes of analysis and prediction of accumulated occupational risks, besides facilitating communication and collaboration with patients. The software developed through the programming language C #, with a SQL SERVER 2012 database engine. Its functionality documented and the Iterative - Incremental Model was used, which is characterized by having a standard framework, widely used to the analysis, implementation and documentation of object-oriented systems. The main phases of this model are: Analysis, Design, Implementation, Testing, Deployment and Maintenance, they allow the development of the systems quickly and efficiently with the aim of delivering quality software that meets the needs of the client; it also helps to keep the development of each requirement specified by the user in an orderly manner. As a result, there is software of periodic medical records for the analysis and prediction of accumulated labor risk composed of the following modules: User Profiles for Authentication, Managing Patients, and Data Recording for Accumulated Occupational Risk Analysis, Register Physical Examination, Record Habits, Generate ASSIST Questions, Manage Data Maintenance Tables, Consult Clinical Summary, and Generate Medical Certificate. The system is currently installed and is functioning efficiently, which is why it has the respective implementation guarantee.